Uso da modelagem da informação da construção para subsidiar a gestão do ambiente construído - Bruno Cesarino Soares (2021)
Building information modeling (BIM), in addition to representing three-dimensional models, can be understood as a database to store information about the entire life cycle of a construction, therefore being a repository and source of consultation for the management of projects involving the built environment. The assets contained in a built environment include architectural and engineering projects, technical drawings, spreadsheets, schedules, reports, construction components, their elements and several other results of the services performed in the construction works. The organization of information about these assets is based on the need to represent them in a unique and efficient way in a BIM environment, using a standardized classification system. The research aimed to evaluate the use of BIM modeling to support the management of the built environment, observing the relevant normative and regulatory instruments. The study contains an analysis on the use of construction information classification systems (Construction Information Classification System - CICS) that apply to BIM modeling, such as the system defined by the Brazilian technical standard ABNT NBR 15965. The organization of information using a CICS as proposed by the Brazilian standard is one of the requirements to support the digital transformation of the Architecture, Engineering and Construction (AEC) industry. A computational prototype was conceived and implemented to evaluate the use of a CICS in the context of BIM modeling. The prototype performs a mechanism for checking rules in BIM models to assess their compliance with the use of a CICS and was implemented as an extension application (add-in) for a BIM software platform. The development followed an evolutionary cycle according to the Action Design Research (ADR) approach. The proposed formulation was evaluated and validated through a case study that consisted of the execution of the prototype implemented in BIM models of the building complex of the former UFMG School of Engineering (EEUFMG) to verify its compliance with the use of Brazilian CICS. With the developed solution it is also possible to evaluate the use of other CICS. The results showed that the formulation can be used as a subsidy for the generation of indicators of the quality of the information modeled using the BIM methodology and a CICS. These indicators can be evaluated throughout the life cycle of the built environment, allowing the development of an information system or, more broadly, a knowledge organization system (KOS) applied to the management of the built environment.